Formation of Similar Users group by using Support Vector Machine with Facebook Posts - Mohankumar, K; Srinivasan, B (International Journal of Computer Sciences and Engineering, 2019)
Users of Online Social Network (OSN) generate their own post by using texts, images, videos and resources like emojis, stickers etc., Among the different types of posts, the text content can easily be interpreted by other and exposes the full thoughts of a user towards a topic. This paper attempts to group similar users, who produced the same text posts towards a set of pre-defined topics. The similarity among users with their posts is calculated with the aid of linear Support Vector Machine (LinearSVM) classifier and the performance is evaluated.